Supporting Students at the Transition to University with a Self-Paced, Online Mathematics Induction Course - Parkes, Abigail; Naughton, Liam; Karodia, Nazira; Brennan, Jordan; Rodden, Emily (MSOR Connections, 2023)
In this article we report on the design, development, and delivery of an online, self-paced, Mathematics Induction Course given to all incoming students in the Faculty of Science & Engineering at the University of Wolverhampton. We outline the background to the project, and we report on some preliminary findings which will be used to inform the future delivery of this course.